2021
DOI: 10.2174/1573398x17666210831160728
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Uphill and Downhill Eerobic Exercises on Serum Apolipoprotein A1 and Apolipoprotein B Levels and their Ratio in Patients with Chronic Obstructive Pulmonary Disease

Abstract: Background: Chronic obstructive pulmonary disease (COPD) is a major health issue worldwide. Introduction: This study aimed to evaluate the effect of aerobic exercises at steep surfaces on Apo A1 and Apo B serum levels and their ratio in COPD patients. Methods: This interventional study was undertaken on 16 COPD patients. The sample was selected by using the random sampling method. Patients were randomly divided into 2 groups of 8 members: uphill and downhill. Spirometry was conducted prior to the exerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In the present study, AT + DE reduced plasma Apo B level probably by reducing the production of Apo B‐containing lipoproteins. Apo A‐1 is a critical component of HDL‐C and the previous studies showed that long‐term exercise training increased the synthesis of Apo A‐1 and reduced its catabolism (Whyte et al, 2020; Yazdani et al, 2018). However, in this research, there was no significant increase in Apo A‐1.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, AT + DE reduced plasma Apo B level probably by reducing the production of Apo B‐containing lipoproteins. Apo A‐1 is a critical component of HDL‐C and the previous studies showed that long‐term exercise training increased the synthesis of Apo A‐1 and reduced its catabolism (Whyte et al, 2020; Yazdani et al, 2018). However, in this research, there was no significant increase in Apo A‐1.…”
Section: Discussionmentioning
confidence: 99%
“…Han et al showed that ApoA1 can stimulate glucose uptake in C2C12 myotubes [65]. Furthermore, previous studies have shown that exercise increases levels of ApoA1 in humans [66], [67]. The discrepancy in results could be the due to the type of exercise/species model used – we used an in vitro model of chronic stimulation using murine cells, whereas others used plasma from humans after weeks of aerobic exercise.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it cannot be proven that this mechanism directly reduces lipoprotein levels, which are risk factors of CVD. Following aerobic exercise, ApoA-I levels were elevated in patients with chronic obstructive pulmonary disease [ 64 ]. Moreover, in CVD, exercise training directly affected not only traditional cardiovascular risk factors, but also vascular function and structure [ 65 ].…”
Section: Discussionmentioning
confidence: 99%